Factors associated with sedentary behaviour in adults during the covid-19 pandemic - Bruno de Freitas Camilo; Paulo Ricardo Prado Nunes; Gabriela Baranowski-Pinto; Gislaine Cristina Souza; Camila Rosa de Oliveira; Brandel José Pacheco Lopes Filho (INFAD, 2023)
In recent decades, sedentary behavior (SB) has come to be understood as an important public health problem. The confinement imposed by the COVID-19 has modified people’s lifestyle, including increased time in SB, which is a risk factor for several health problems. In this context, the aim of this study was to analyze the association between sociodemographic, behavioral and health conditions factors with SB in adults during the COVID-19 pandemic. This is an observational and cross-sectional study that analyzed 510 Brazilians aged ≥ 18 years. Participants answered an online questionnaire containing sociodemographic, behavioral and health status information. Individuals with high SB had a lower level of physical activity (PA), higher scores of anxiety, depression and stress, perception of poor health and health problems. In Logistic Regression, model 1 showed that being insufficientlyactive(OR 1.96; 95% CI: 1.31 – 2.93), having poor health perception (OR 1.67; 95% CI: 1.09 - 2.57) and having a health problem (OR 1.79; 95% CI: 1.19 - 2.68) was associated with high SB. However, for model 2, only insufficient levels of PA (OR 1.78; 95% CI: 1.15 – 2.75) and health problem (OR 1.83; 95% CI: 1.10 - 3.05) remained associated with SB. These findings highlight the importance of staying physically active and reducing SB as a strategy for health promotion.